Exploring Cefiderocol Resistance Mechanisms in Burkholderia pseudomallei - Carina M., Hall; Nawarat, Somprasong; Johannah P., Hagen; Roxanne, Nottingham; Jason W., Sahl; Jessica R., Webb; Mark, Mayo; Bart J., Currie; Yuwana, Podin; David M., Wagner; Paul, Keim; Herbert P., Schweizer (American Society For Microbiology, 2023)
Cefiderocol is a siderophore cephalosporin designed mainly for treatment of infections caused by β-lactam and multidrug-resistant Gram-negative bacteria. Burkholderia pseudomallei clinical isolates are usually highly cefiderocol susceptible, with in vitro resistance found in a few isolates. Resistance in clinical B. pseudomallei isolates from Australia is caused by a hitherto uncharacterized mechanism. We show that, like in other Gram-negatives, the PiuA outer membrane receptor plays a major role in cefiderocol nonsusceptibility in isolates from Malaysia.